Penerapan Media Komik Strip untuk Meningkatkan Hasil Belajar Siswa Berdasarkan Teori Kognitif: Penelitian - Nuraini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe and analyze the effectiveness of comic strip media in improving fifth-grade students’ cognitive learning outcomes in the Science and Social Education (IPAS) subject. This research was driven by low student achievement resulting from the dominance of lecture-based teaching methods and the lack of engaging learning media. Based on cognitive learning theory, students require visual stimuli and meaningful learning experiences that connect new information with prior knowledge. A qualitative descriptive approach was employed through classroom observations, documentation, expert validation, and analysis of pre-test and post-test scores. The comic strip media was developed following the cognitive principles of Piaget, Ausubel, and Bruner and was designed to support visual learning suited to the concrete operational stage of elementary students. The findings indicate a significant increase in students’ scores, with N-gain categorized as moderate to high. Student engagement also increased, as shown by their active participation in reading, discussing, and interpreting story panels. These results demonstrate that comic strips effectively enhance students’ cognitive processes, motivation, and understanding of IPAS concepts through concrete and contextual visual representation elementary school.